Biomedical scientific publication patterns in the Scopus database: a case study of Andalusia, Spain - Chinchilla-Rodríguez, Zaida; López-Illescas, Carmen; de Moya-Anegón, Félix (Revista Cubana de Información en Ciencias de la Salud, 2012)
This paper characterises scientific output in biomedicine in Andalusia, and Spain as a whole, and conduct a first-time comparison to Europe- and world-wide production. The data were extracted from the Scopus database. Three families of indicators are explored to analyse research quantity, quality and collaboration. The results show an upward trend on biomedical output in Andalusia. Over 50 % was in clinical medicine, whose growth doubled the basic medicine. We found greater than nationwide specialisation in biochemistry, genetics and molecular biology, immunology and microbiology, and pharmacology, while psychology proved to be the most prominent emerging area. The publication in most cited journals together with national and international collaboration enhanced research visibility. More citable papers were published on basic than clinical medicine, and the number of citations received by the former was also larger. The higher citation rate in basic medicine may also be explained by the bigger percentage of papers published in international instead domestic journals. Hence, publication patterns would appear to affect research visibility. The methodology proposed may provide guidance for public policy makers to improve, encourage and intensify good biomedical research practice.